Strategi Koping Remaja Mengatasi Kesepian - Agung Budi Nurrahman; Lisya Chairani (Psychopolytan : Jurnal Psikologi, 2024)
Loneliness is a mental health issue. The aim of this research is to understand how adolescents recognize, feel and overcome loneliness. The research was conducted using a descriptive qualitative approach, involving 38 adolescent (21 girls and 17 boys) who experienced loneliness in three junior high schools (SMP) in Pekanbaru. The data was obtained through online interviews using Google Form. Data analysis uses thematic analysis techniques. The results showed that junior high school adolescents used various coping strategies to overcome loneliness. The most commonly used strategy in grades 8 and 9 is focusing on emotions, while in grade 7 focuses more on problems. The results of this research provide an overview of loneliness and how to overcome it from an adolescent perspective so that it can help the process of counseling and therapy for loneliness in adolescents. Further research is needed to understand the factors that influence adolescents' coping strategies in overcoming loneliness.